Biodistribution and anti-tumor efficacy of doxorubicin loaded glycol-chitosan nanoaggregates by EPR effect - Son, YJ; Jang, JS; Cho, YW; Chung, H; Park, RW; Kwon, IC; Kim, IS; Park, JY; Seo, SB; Park, CR; Jeong, SY (ELSEVIER SCIENCE BV, 2003)
An in vivo tumor targeting test of glycol-chitosan nanoaggregates was carried out with FITC-conjugated glycol-chitosan nanoaggregates (FTC-GC) and the doxorubicin conjugated glycol-chitosan (GC-DOX). To investigate its biodistribution in tumor-bearing rats, glycol-chitosan was labeled with fluorescein isothiocyanate (FITC), which formed nanoaggregates with a diameter of about 250 nm in aqueous media. GC-DOX nanoaggregates containing acid-sensitive spacers were prepared. The GC-DOX formed micelle-like nanoaggregates spontaneously in aqueous media. GC-DOX nanoaggregates had a narrow and unimodal size distribution, and its hydrodynamic diameter measured by dynamic light scattering ranged from 250 to 300 nm. A loading content of doxorubicin into GC-DOX nanoaggregates as high as 38%, with 97% loading efficiency, could be obtained using a physical entrapment method. A tumor-bearing animal model was developed by inoculating tumor cells into the back of a rat. The FTC-GC nanoaggregates were injected into the tail vein of tumor-bearing rats and their tissue distribution was examined. The FTC-GC nanoaggregates were distributed mainly in kidney, tumor and the liver and were scarcely observed in other tissues. They were maintained at a high level for 8 days and their distribution in tumor tissues increased gradually. This suggests that chitosan nanoaggregates accumulate passively in the tumor tissue due to the enhanced permeability and retention (EPR) effect. Doxorubicin loaded GC-DOX nanoaggregates (DOX/GC-DOX) were injected into the tail vein of tumor-bearing rats and their anti-tumor effect was examined. Tumor growth was suppressed over 10 days. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: N-SUCCINYL-CHITOSAN; BLOCK-COPOLYMER MICELLES; POLYMERIC MICELLES; MACROMOLECULAR THERAPEUTICS; PHYSICAL ENTRAPMENT; CANCER-CHEMOTHERAPY; ANTICANCER ACTIVITY; IN-VIVO; DRUG; ADRIAMYCIN